Carbon sequestration and ecosystem services. Evidence from the functional urban area of Cagliari, Italy - Lai, Sabrina; Zoppi, Corrado (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Carbon sequestration and storage, i.e., the process whereby carbon dioxide is removed from the atmosphere by plants and stored in natural reservoirs such as soil or water pools, is a key regulating ecosystem service (ES) that contributes to mitigating climate change and its impacts. Its positive and negative relationships with other ESs, i.e., respectively, synergies and trade-offs, are yet to be fully understood, especially at the urban level. Therefore, this study proposes a methodological approach that integrates ES modeling and mapping with inferential models, with a view to identifying and assessing the relationships between carbon sequestration and storage and other ESs. The implementation of the proposed approach in the context of the Functional Urban Area of Cagliari (Italy) puts in evidence a positive and significant relationship between carbon sequestration and storage and other regulating ESs, i.e., pluvial flood retention, local temperature regulation, and habitat quality; to the contrary, a negative but quantitatively negligible relationship is unveiled as far as the potential supply of nature-based recreation is concerned. Relevant planning implications are identified based on these outcomes, which highlights the significance and usefulness of the proposed approach for planners and policy makers.